Cardiorespiratory responses during exercise in competitive in-line skaters - Fedel, F. J.; Keteyian, S. J.; Brawner, C. A.; Marks, C. R.; Hakim, M. J.; Kataoka, T. (Medicine & Science in Sports & Exercise, 1995)
Male competitive in-line skaters were measured physiologically to determine parameters associated with performance economy at various speeds and stroking frequencies. Skater-selected stroking frequencies resulted in a more economical energy utilization than imposed frequencies. Body position was also found to favor economy with skaters preferring a bent-over body position to an upright position. Implication: In cyclic activities, such as skating, running, rowing, swimming, and cycling, there is an optimal rate of movement that is associated with physiological economy. Higher or lower rates decrease that economy. Similarly, the posture of performance is a self-selecting element with most individuals able to determine the body position that yields the best movement economy.